Brightness discrimination in budgerigars (Melopsittacus undulatus). - Olle Lind; Sandra Karlsson; Almut Kelber (PLoS ONE, 2013)
Birds have excellent spatial acuity and colour vision compared to other vertebrates while spatial contrast sensitivity is relatively poor for unknown reasons. Contrast sensitivity describes the detection of gratings of varying spatial frequency. It is unclear whether bird brightness discrimination between large uniform fields is poor as well. Here we show that budgerigars (Melopsittacus undulatus) need a Michelson contrast of 0.09 to discriminate between large spatially separated achromatic fields in bright light conditions. This is similar to the peak contrast sensitivity of 10.2 (0.098 Michelson contrast) for achromatic grating stimuli established in earlier studies. The brightness discrimination threshold described in Weber fractions is 0.18, which is modest compared to other vertebrates.